Feasibility Analysis of Using Electronic Vehicles at Grab Indonesia with the IRR Method - Furqan, Muhammad Alif; Sahbandar, Aulia Idharizqi Widayani; Barandika, Barandika; Rumalutur, Yizri Ievana Febrianty; Abid, Rasyid; Sutisna, Fazar; Iskandar, Yelita Anggiane; Vikaliana, Resista (Proceeding Mercu Buana Conference on Industrial Engineering, 2023)
Indonesia is a country with the fourth largest population in the world, reaching 275.77 million people in 2022. This has caused the need for transportation to increase, thereby creating new business opportunities for public transportation companies, including online motorcycle taxi companies such as Grab which provide service gates - to-door and order food delivery. However, the increase in transportation needs also causes an increase in fuel consumption, one of the factors causing air pollution. This study aims to calculate and determine the feasibility of using electric vehicles by Grab drivers to transport passengers, goods, or food while calculating the carbon emissions created as a result of these various activities. The feasibility analysis is based on the Internal Rate of Return (IRR) of each type of transport vehicle used, using the Sum of Years Digits (SOYD) method, which takes into account depreciation, fuel use, and the carbon emissions produced. The results of the study show that the use of electric vehicles is a viable investment in the long term, both technically and financially.